A Endothelium-derived extracellular vesicles promote splenic monocyte mobilisation in myocardial infarction. (5th June 2017) - Akbar, Naveed; Digby, Janet E; Cahill, Thomas J; Tavare, Abhijeet N; Saluja, Sushant; Dawkins, Sam; Edgar, Laurienne; Rawlings, Nadia; Ziberna, Klemen; McNeill, Eileen; Johnson, Errin; Aljabali, Alaa A; et al.
Abstract : Background: Following acute myocardial infarction (AMI), monocytes are rapidly mobilised from the spleen to peripheral blood, from where they undergo transcriptional activation and infiltrate injured tissue, with potential to contribute to both injury and repair. The mechanism by which the injured myocardium signals splenic-monocyte mobilisation remains poorly understood. Recent work shows extracellular vesicles (EV, which carry proteins, microRNA/mRNA) are a means of rapid cell-to-cell communication, which, combined with knowledge of their composition and propensity to be taken up by other cells, suggests a possible role in signalling. Here we show that AMI results in a net increase in circulating endothelial cell (EC)-EV that induce splenic monocyte motility in vivo and cellular transcription. Methods: Platelet-poor plasma was collected from patients with ST-segment elevation-AMI (STEMI) and mice subjected to AMI. EV were isolated by ultra-centrifugation and analysed for size/number by Nanoparticle Tracking Analysis, western blot (EV-markers: ALIX, TSG101, CD69, CD9 and Hsp70), ELISA for EC markers (CD31, ICAM-1, P-selectin, E-selectin and VCAM-1), electron microscopy and for EV-miRNAs. Human and mouse EC were used in vitro to evaluate EV release, injected into wild-type or CD68 GFP+ naïve mice to assess bio-distribution, splenic-monocyte mobilisation, uptake by monocytes, cellular mRNA transcription and cell motility. Results: Acutely (24 hours) after AMI there is a significant increase in circulating EV in humans (p<0.01) and mice (p<0.001) that later subsides. Plasma EV number correlates with myocardial injury in humans (R2=0.52, p<0.01). Plasma EV display EC-surface markers and show enrichment for vascular cell adhesion moleculae-1 (VCAM-1) in AMI (p<0.05). In vitro pro-inflammatory cytokines significantly increase EV production by EC, whereas 'anti-inflammatory' IL-4 and IL-6 had no effect. Inflammatory-EC-EV displayed significant enrichment of VCAM-1 (p<0.05). In-vitro labelled EC-EV accumulate in monocytes. Inflammatory-EC-EV significantly enhanced macrophage chemokineses (p<0.05) and chemotaxis to MCP-1 (p<0.05), a response that was abolished by pre-incubating EC-EV with an anti-VCAM-1 antibody (p<0.05). Injected labelled EC-EV accumulate in the spleen, interact with splenic monocytes and induce splenic-monocyte mobilisation and peripheral monocytosis in-vivo (p<0.01). Human plasma-EV show enrichment for 12 miRNAs in AMI, including EC-associated miR-126–3p/5p. miRNA-mRNA target gene prediction and functional enrichment analysis show roles for these miRNAs in the positive regulation of chemotaxis, cellular growth and proliferation. EC-EV significantly induced alterations in mRNA of motility genes by reducing PLEXIN-B2 (p<0.001), a negative regulator of motility and increasing ITGB2 (p<0.001) expression in monocytes. In conclusion: (1) AMI surges plasma EV; (2) Plasma-EV protein composition is consistent with EC origin. (3) Injected EV localise to the spleen and (4) mobilise splenic monocytes. (5) In culture, EC increase EV release, enhance monocyte motility and (6) regulate genes that are important in cellular movement. These demonstrate a novel role for EC-derived EV in monocyte activation after AMI.